2000
DOI: 10.1038/sj.bjp.0703732
|View full text |Cite
|
Sign up to set email alerts
|

Collar‐induced elevation of mRNA and functional activity of 5‐HT1B receptor in the rabbit carotid artery

Abstract: 1 Hypersensitivity to serotonin (5-HT) develops in rabbit collared carotid arteries. Previous data demonstrated the involvement of 5-HT 1 -like receptors which are not active in normal carotid arteries. This study investigated the interaction in the rabbit carotid artery between 5-HT and a moderate tone as this can uncover functional 5-HT 1 -like receptors. Furthermore, the expression of messenger RNA (mRNA) and protein of 5-HT 1B , 5-HT 1D and 5-HT 2A receptors was addressed. 2 Silicone collars were placed ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Intriguingly, in one of these two patients, in a small branch of artery which was collared but not occluded by surrounding fibrotic connective tissue, the sensitivity to and E max for sumatriptan were much higher than those in the uncollared normal small branch of the same patient. This observation is in accordance with the study of Geerts et al (2000) that placement of a collar on the rabbit carotid artery raised the amount of 5-HT 1B mRNA and receptor density, resulting in increased sensitivity to 5-HT. Pretension in our study was about 15 mN just before the start of the experiments, as opposed to 2 mN in the study of Nilsson et al (1997) in which no contraction to sumatriptan was detected.…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, in one of these two patients, in a small branch of artery which was collared but not occluded by surrounding fibrotic connective tissue, the sensitivity to and E max for sumatriptan were much higher than those in the uncollared normal small branch of the same patient. This observation is in accordance with the study of Geerts et al (2000) that placement of a collar on the rabbit carotid artery raised the amount of 5-HT 1B mRNA and receptor density, resulting in increased sensitivity to 5-HT. Pretension in our study was about 15 mN just before the start of the experiments, as opposed to 2 mN in the study of Nilsson et al (1997) in which no contraction to sumatriptan was detected.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the findings of previous studies (Ü stu¨nes et al 1996; Kerry et al 1999), collaring increased the pD 2 values of 5-HT in arteries, a characteristic feature of the collar model (De Meyer et al 1990Hickey et al 1996). As stated before, the 5-HT 1B receptor subtype has been found to be responsible for the development of hypersensitivity to 5-HT in the collar model (Geerts et al 1999(Geerts et al , 2000. With regard to the effect of TAK-044 on 5-HT-induced contractions, chronic treatment with TAK-044 (21 days) seems to enhance the E max values of 5-HT without affecting pD 2 values in both collared and sham arteries.…”
Section: Contractionsupporting
confidence: 91%
“…In 1999, in this model, Geerts et al demonstrated that the serotonergic receptor involved in the hypersensitivity to 5-HT of rabbit collared carotid artery is a 5HT 1B receptor subtype (Geerts et al 1999). Morover, Geerts et al (2000) further reported that collar placement elevates mRNA expression and activity of the 5HT 1B receptor in the rabbit carotid artery. In our study, consistent with previous results (De Meyer et al 1994;Ü stu¨nes et al 1996;Kerry et al 1999;Yasa et al 1999), the collar placement suppressed 120 mM KCl-induced contractions in collared rabbit carotid arteries.…”
Section: Contractionmentioning
confidence: 95%
“…Then the lysates were clarified by centrifugation (10 000 g, for 10 min at 4°C). The protein content of the supernatant was determined by the standard method of the bicinchoninic acid (BCA) [24]. Samples (60 lg protein) were boiled for 5 min in a denaturizing solution (200 mM Tris- [30][31][32][33][34][35][36][37][38][39][40] min, in 100 mM Tris-base, 100 mM bicine, 0.1% (w/v) SDS buffer], and electroblotted onto a polyvinyl difluoride (PVDF) membrane (Roche) in 96 mM glycine, 12.5 mM Tris-base and 20% (v/v) methanol cooled transfer buffer (overnight at 40 V and 10°C).…”
Section: Western Blot Analysismentioning
confidence: 99%